E-learning challenges as perceived by communities of practice: Open University Malaysia's experiences - Kaur, Abtar; Ansary Ahmed, (Asian Association of Open Universities (AAOU), 2006)

(untitled)
E-learning has become ingrained in conversations that border around learning, however, how much and how effectively e-learning is practiced and understood is an issue that needs further investigation. This paper will first provide an overview of e- learning practices in Malaysia followed by detailed findings of e-learning practices at Open University Malaysia. Findings of a survey done on 26 Malaysian organizations show that only 4% truly practice some form of e-learning. Nevertheless most participants in the survey noted that e-learning will be the preferred choice in time to come. The survey also shows that most organizations are still very comfortable with a blended style of learning or training. Findings of a research conducted at Open University Malaysia (OUM) shows that as a new player in e-learning initiatives, the OUM has achieved much especially in ensuring that its over 30,000 students are practicing some form of e-learning. At OUM, although self-managed and face-to-face learning are the preferred choices, much effort and resources are pumped into e- learning in ensuring that OUM has the right mix for its blended mode. The paper will present a report on findings of e-learning and explicate issues within to determine how e-learning efforts can be further refined to support the overall blended pedagogy practiced at OUM. (Auhors' abstract)